Lean and Green Manufacturing Towards Eco-Efficiency and Business Performance - Mathiyazhagan, Kaliyan; Vimal, K. E. K.; Kumar, Harish; Ramesh, Anbanandam; Agarwal, Vernika; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides a stage-by-stage integration of lean and green manufacturing paradigms to achieve environmental and economic benefits. The book includes chapters on conceptual development for incorporating the lean and green paradigm, and methods, tools and techniques for developing and integrating lean manufacturing. Several case studies which demonstrate the benefits of integrating lean and green manufacturing techniques are also covered here. The contents of this book are expected to support researchers and practitioners in the implementation of integrated lean and green manufacturing technologies. .
Analyzing the barriers for the implementation of lean and green closed-loop supply chain in Indian SMEs -- Assessing the Drivers and Challenges to Deploying Lean-Green practices the in Indian Manufacturing Sector -- Performance Evaluation of Lean Green Healthcare Manufacturing Plants: A Fuzzy TOPSIS Approach -- Impact of policy change on Sustainability initiatives by Indian firms -- Trade prediction outcomes during pandemic and its impact in lean implementation.
Keywords: Manufactures; Industrial Management; Environmental sciences -- Social aspects; Production management; Operations research; Artificial intelligence; Machines, Tools, Processes; Industrial Management; Environmental Social Sciences; Operations Management; Operations Research and Decision Theory; Artificial Intelligence; Lean manufacturing; Manufacturing processes -- Environmental aspects; Sustainable engineering